KECERDASAN JAMAK DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - SESMIARNI, ZULFANI (Universitas Islam Negeri Raden Intan Lampung, 2014)
Human resource potensial is an asset and development of human capital in Indonesia Potential proficiency level can be extracted through education and learning. Learning is an attempt to develop the potential of learners that can be turned into competence. One of the potential possessed by learners is multiple intelligences. In the process of learning science in elementary school teacher during treatment and still provide the same educational services to all students. Whereas needs of learners should be served with a variety of ways according to its characteristics. It is necessary for an understanding of the multiple intelligences in learning science in elementary school, so it can stimulate the intellectual potential of each individual stands on learners. This research was conducted at the elementary school in the district Sijujung by questionnaire. The results of the study noted that the 5th grade elementary school students generally already have multiple intelligences that stands out with many variations on each learner.